2014 IEEE 26th International Conference on Tools With Artificial Intelligence 2014
DOI: 10.1109/ictai.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of UAV Control Rules for Spraying Pesticides on Crop Fields

Abstract: Abstract-The use of pesticides in agriculture is essential to maintain the quality of large-scale production. The spraying of these products by using aircraft speeds up the process and prevents compacting of the soil. However, adverse weather conditions (e.g. the speed and direction of the wind) can impair the effectiveness of the spraying of pesticides in a target crop field. Thus, there is a risk that the pesticide can drift to neighboring crop fields. It is believed that a large amount of all the pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 18 publications
0
42
0
1
Order By: Relevance
“…It consists of using pulverization devices to spread a certain type of pesticide or fertilizer to provide a better result for the harvest. This kind of production enhancement can provide increased productivity, improved quality and significant reduction of costs in large scale [12].…”
Section: Crop Pulverizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of using pulverization devices to spread a certain type of pesticide or fertilizer to provide a better result for the harvest. This kind of production enhancement can provide increased productivity, improved quality and significant reduction of costs in large scale [12].…”
Section: Crop Pulverizationmentioning
confidence: 99%
“…The airborne approach enables the coverage of much bigger areas at the price of a bigger waste because of not addressing only the necessary areas or due to the lack of accuracy and wind influence [12]. Ground based machines can be used for this purpose but this, in turn, has other challenges.…”
Section: Crop Pulverizationmentioning
confidence: 99%
“…Bruno S. Faiçalatc. [18] have studied the spraying pesticides for protecting crops and to maintain the quality and quantity of crop yield. The application of these pesticides by using aerial vehicles increases the speed of the activity and avoids packing of the soil.…”
Section: ©Ijraset: All Rights Are Reservedmentioning
confidence: 99%
“…While it is common to use buffer zones to mitigate the damage caused by drift, this hazard can occur 5 to 32 km downwind , which far exceeds the range of the buffer zones. The use of UAV rotorcraft has been investigated as a safe and high-precision alternative for spraying pesticides (Bae and Koo, 2013, Faiçal et al, 2014a). This occurs because these aircrafts have no pilots on board and their downwash effect 2 is directed to the plantation (Hanson, 2008).…”
Section: Aerial Sprayingmentioning
confidence: 99%
“…On making a determined convergence, the configuration stage is finalized and the algorithms are evaluated with their respectively defined configurations, in an individual way. The configuration for the PSO algorithm, set out in Faiçal et al (2014a), was not recommended by the GridSearch technique but was included in the experiments of this study, because it is concerned with a solution that is found in the literature and employed as a basis for evaluation.…”
Section: Introductionmentioning
confidence: 99%